Beautiful news : positive trends, uplifting stats, creative solutions - McCandless, David, ....- (New York : Harper Design, 2022)
In this fascinating follow-up to the bestselling Information is Beautiful and Knowledge is Beautiful, the king of infographics David McCandless uses spectacular visuals to give us all a bit of good news.
Keywords: Data visualization; Infographics; Trends